286 Appalachian Kentucky Rural Research Hub: Ensuring the success of community-engaged research - Ashley Hall; G. Mudd-Martin; D.A. Gross; V Fairchild; C Curtis (Journal of Clinical and Translational Science)
Objectives/Goals: To facilitate engagement between university researchers and Appalachian Kentucky communities, the UK Rural Research Hub (RRH) promotes Community Engaged Research (CEnR) and academic–community partnerships that have the greatest potential to conduct impactful research to improve health and reduce regional health disparities. Methods/Study Population: Through the UK RRH, a wealth of expertise and a range of services sustain successful CEnR. Hub coordinators provide research consultations, accelerate researchers’ engagement with the community, and facilitate the success of studies through study coordination, assistance with participant recruitment, data collection and interventions, and through dissemination back to the community. Results/Anticipated Results: UK RRH coordinators have supported numerous studies across the region. For example, RRH staff facilitated recruitment of and collected data from 40 Appalachian caregivers of patients with Alzheimer’s disease and related dementias (ADRD) in a study to improve home environments for patient well-being. The study provided pilot data for a successful K23 application. Other examples of supported research include studies to improve cancer screening uptake, self-management of diabetes, and cardiovascular disease risk reduction, resulting in improved care in the community and often providing pilot data leading to larger national grants. Discussion/Significance of Impact: Research addressing the complex health issues that burden Appalachian Kentucky requires community engagement to be successful. The UK RRH is at the heart of successful CEnR that benefits researchers and communities alike.